Pengembangan Usaha "Kirana Handmade Soap" Melalui Pemanfaatan Teknologi Informasi sebagai Upaya Peningkatan Profitabilitas - Bakhtiar, Yohan; Izzah, Abidatul; Eliyen, Kunti; Nurlina, Nila; Kusuma, Selvia F. (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The product of Handmade Soap (soap that made by home industry using herbal) is a business that requires expertise in chemical compounding. Production of the herbal soap should be handled by qualified chemist, pharmacist, or pharmaceutical technical personnel. A pharmacist from Bhayangkara Hospital Kediri, Qurrota A’yunin, S.Farm, Apt. has ability in manufacturing of the handmade soap. But, the main problem is marketing, because it has not done to public society. Therefore, many people do not recognize about this product eventhough it has quality with good planning. To overcome this problem, we create web-based portal for marketing in kiranahandmade-soap.com and mentoring in marketing using social media through In-house Training, for instance, by posting attractive and persuasive ads. The result of this community service program is web company profile that able to be accessed on https://kiranahandmadesoap.com, facebook account “Sabun Kirana” and Instagram account “@sabunkirana”. Furthermore, after mentoring activity, in fact there has not been a significant increase in profitability, because the digital marketing activities are still running for 2 months. Although the number of selling is stagnant, the marketing media helped in expanding the information about Kirana Handmade Soap.